Czysta propaganda, czy wielka sztuka, patriotyzm i obywatelskie zaangażowanie – jak Ajschylos oraz Eurypides używali swoich fabuł, by wspomóc Ateńską politykę wobec sojuszników - Śmiechowicz, Olga (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
In this article I would like to focus on one research topic: how ancient tragedians manipulated their drama plots (based on Greek mythology) so as to use them for influencing Athenian “international policies.” Those were not any mistakes or airs of nonchalance on the part of the Athenian tragedians; it was just their carefully premeditated strategy of creating persuasive messages to function as pure propaganda. I am chiefly directing my attention to the topic of how the Athenians established their relations with the allies. Meaning the closest neighbours as well as some of those who did not belong in the circle of the Hellenic civilization. I have decided to devote all of my attention to Aeschylus’ and Euripides’ works, as both of them were obvious supporters of the democratic faction. I focused my attention on the texts: Aeschylus: The Suppliants, Oresteia; Euripides: Heracleidae, Andromache, Archelaus,Temenos.